KORELASI HbA1c DAN GULA DARAH PUASA TERHADAP RASIO TG/HDL-K PASIEN DIABETES MELLITUS TIPE 2 BERETNIS JAWA - Yanuarita Tursinawati; Sakinah; Zulfachmi Wahab; Arum Kartikadewi (Bina Generasi : Jurnal Kesehatan, 2023)
Background : Most of the causes of death in type 2 Diabetes Mellitus (T2DM) are coronary heart disease (CHD) with dyslipidemia as one of its risk factors. The best marker for early detection of dyslipidemia is the ratio of triglycerides to high-density lipoprotein cholesterol (TG/HDL-C). In T2DM patients, glycemic control in the form of Fasting Blood Sugar (GDP) and HbA1c can be done to avoid the risk of CHD. This study aims to identify the correlation of Hba1c and GDP with the ratio of TG/HDL-K in T2DM patients with Javanese ethnicity.Methods : This research was a cross sectional study involving 107 respondents from several health centers in Semarang City with consecutive sampling method. GDP, HbA1c, and TG/HDL-K ratio were obtained from medical records. Spearman correlation statistical test was used with a significance value of p <0.05. Results: The average HbA1c (7.86 ±1.97%), GDP (160.36± 76.82gr/dL), and the TG/HDL-K ratio (3.50± 2.22) exceeded the normal number. There was a weak significant correlation between GDP and the TG/HDL-K ratio (p=0.020; r=0.224) and there was no correlation between HbA1c and the TG/HDL-K ratio (p=0.549; r=0.059) in T2DM patients with Javanese ethnicity.Conclusion: The GDP of Javanese T2DM patients is weakly correlated with the TG/HDL-K ratio but not with HbA1c. Glycemic control is needed as an early marker of CHD risk in T2DM.